INTRUSI AIR LAUT PANTAI BAROMBONG MAKASSAR DENGAN METODE KONDUKTIVITAS LISTRIK - Yanti, Haswida; Arsyad, Muhammad (Universitas Negeri Makassar, 2016)
We reported the coastal sea water intrusion of Barombong Beach Makassar by using electrical conductivity method. The purpose of this study was to analyze the occurrence of intrusion of sea water wells along Barombong beach area of Makassar and identifying the citizen well water in terms of its physical properties. To determine the level of seawater intrusion in wells, it was been conducted the measurment of electrical conductivity (EC) of the water wells. Sample of well water took at home inhabitants of coastline that was 500m-1500m far. Based on the results of testing that was done on 15 samples taken from populations’ wells in Barombong, Tamalate District, it has been known that the intrusion of seawater has reached the area 3. In area 1, the water was brackish and even salty category, area 2 was in the category of slightly brackish water as well as in the region 3. From the analysis of the observation results it could be seen that conductivity was decreasing with the increasing of distant regions from the waterfront and vice versa, the value of conductivity was increasing when the distance was closer to the waterfront. The water quality, based on its physical condition, was of temperatures ranging from 29,5oC to 33,0oC and the degree of acidity (pH) of the entire sample was alkaline.Keywords : sea water intrusion, water wells, electrical conductivityTelah dilakukan penelitian mengenai Intrusi Air Laut Pantai Barombong Makassar dengan Metode konduktivitas listrik. Tujuan penelitian ini adalah menganalisis besar intrusi air laut sumur warga disepanjang kawasan Pantai Barombong Makassar dan mengidentifikasi air sumur warga ditinjau dari sifat fisiknya di kawasan Pantai Barombong Makassar. Untuk mengetahui tingkat intrusi air laut pada sumur gali, dilakukan pengukuran Daya Hantar Listrik (DHL) air sumur. Pengambilan sampel air sumur dirumah penduduk dari garis pantai yaitu berjarak 500m-1500m. Berdasarkan hasil pengujian yang telah dilakukan terhadap 15 sampel yang diambil dari sumur-sumur penduduk di Pantai Barombong Kecamatan Tamalate diketahui bahwa intrusi air laut sudah mencapai wilayah 3. Pada wilayah 1 air berada dengan kategori payau bahkan asin, wilayah 2 dalam kategori air agak payau demikian halnya pada wilayah 3. Dari analisis pengamatan dapat dilihat nilai konduktivitas menurun seiring dengan semakin jauhnya daerah dari tepi pantai, dan sebaliknya nilai konduktivitas listrik membesar dan meningkat apabila jarak semakin dekat dari tepi pantai.Kualitas air berdasarkan keadaan fisiknya mempunyai nilai suhu berkisar antara 29,5oC - 33,0oC dan untuk derajat keasaman atau (pH) air dari keseluruhan sampel yaitu bersifat basa.Kata Kunci: intrusi air laut, air sumur, konduktivitas listrik